HILAL KHASHAN, Arabs at the crossroads - Salloukh, Bassel F. (2004)
Hilal Khashan's book is a sweeping indictment of the myriad Arab failures since the collapse of the Ottoman Empire and the emergence of the modern Arab state system. It is a story of overwhelming Arab failures at all levels: political, military, developmental, intellectual, cultural, and social. Common to these failures, however, is a basic foundational dislocation—one that has doomed everything Arab. It is the crisis of identity and legitimacy bedeviling Arab society and politics. This crisis is not without cause, however. It is rooted in the decline of traditional forms of political legitimacy and the concomitant failure to replace them with modern ideas, attitudes, and institutions. Consequently, Khashan contends, “Arabs” suffer from “a severe identity crisis” (p. 1), and the “Arab mind” is utterly confused. Moreover, it is this crisis of identity, and its socio-political ramifications, that explain the failure of the “Arabs” in the aforementioned spheres. In fact, and on Khashan's reading, everything that transpires in the Arab world is either caused by the “Arab mind” or has a direct impact on it, but only to confuse it even more.